Next to cross-country skiing, running is the best type of fitness training for all sports - Hamilton, A.
In any sport where it is necessary to propel the body at speed for most of the game, about 50 per cent of muscle mass is used. Theoretically, then, the best type of fitness training for all sport is cross-country skiing, where VO2max readings of 85mls.kg.min for top performers have been recorded. However, a lot of time is needed to learn to ski efficiently and what happens if there's no snow? So we are left with running. Author explains his ideas on fitness training by running for different sports, esp. games.